FORMULASI SEDIAAN GEL PEEL-OFF EKSTRAK BUAH LIMPASU (Baccaurea lanceolate (Miq) Mull.Arg.) SEBAGAI ANTIBAKTERI - Deni Setiawan; Nur Mahdi; Muhammad Riki Shindi Praristiya (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Skin is a protective layer of the body as well as an aesthetic factor to protect from exposure foreign substances and sunlight. Some problems that may arise on the skin include premature aging and acne. The use of natural ingredients as cosmetics is increasing, one of which is the limpasu fruit peel-off gel mask. This study aims to determine the antibacterial activity of the ethanol extract of limpasu fruit extract. The formulation was made with three concentrations of ethanol extract of limpasu fruit (Baccaurea lanceolate) 4, 6 and 8 grams. The formula was tested on E.coli. The yield of limpasu fruit extract was 30.49 grams or 7.81%. Results of preliminary identification of ethanol extract containing saponins and flavonoids. The results of the antibacterial test formulas 1 to 3 had inhibition zones 12, 53; 7.94 and 9.97 mm with a positive control of tetracycline which had an average inhibition zone of 28.87 mm. The peel-off gel formulation had antibacterial activity because the average inhibition zone was more than 6 mm.